2008
DOI: 10.1007/s10815-008-9277-3
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between male age, sperm quality and sperm DNA fragmentation in 320 men attending a fertility center

Abstract: Purpose To investigate the effects of male aging on sperm quality and sperm DNA fragmentation. Methods The ejaculates of 320 unselected men attending a fertility clinic and, as a control, 84 normozoospermic men without any history of ART were analyzed according to WHO guidelines. Sperm DNA fragmentation was measured by flow cytometry after staining with propidiumiodide. Results The patients were divided into four groups: <30 years, 30-35 years, 36-39 years and ≥40 years. Sperm motility decreased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
5
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 28 publications
7
47
5
9
Order By: Relevance
“…Levitas et al (59) added that the most significant reduction in sperm parameters occurred after the age of 55 years old. However it disagrees with those of Chen et al (61); Winkle et al (62). However, in an earlier study they found inverse associations between age and sperm concentration, motility and morphology.…”
Section: Discussioncontrasting
confidence: 67%
“…Levitas et al (59) added that the most significant reduction in sperm parameters occurred after the age of 55 years old. However it disagrees with those of Chen et al (61); Winkle et al (62). However, in an earlier study they found inverse associations between age and sperm concentration, motility and morphology.…”
Section: Discussioncontrasting
confidence: 67%
“…In contrast, Schmid et al [11] using the same methods, reported that male age only influences single strand breaks and age was not associated with sperm DNA damage under neutral conditions, which is thought to represent double strand DNA breaks. Using a modified Nicoletti assay, Winkle et al [12] suggest that the amount of spermatozoa with fragmented DNA is not affected by male age. So we show that the results of literature varied according the technique used, but the majority of studies show a positive relationship between age and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA integrity as assessed by terminal desoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) [6], sperm chromatin structure assay (SCSA) [7,8], and Comet assay [9], were also shown to be compromised with advancing age. However, this notion was not supported by all studies [10][11][12], and the results varied according the technique used for the detection of DNA damage.…”
Section: Introductionmentioning
confidence: 89%
“…[36][37][38][39] Specifically, one study examined 66 men aged 20-57 years and identified significantly more breaks in the sperm DNA of older men (.35 years) compared with that of younger men. 39 Another study by Winkle et al, 40 however, found no significant correlations between male age, semen parameters and sperm DNA fragmentation. These studies are interesting given the potential teratogenic effects of environmental pollutants and chemicals that could accumulate with age.…”
Section: Effect Of Paternal Age On Semen Qualitymentioning
confidence: 96%